PERSEPSI PETANI NILAM TERHADAP PEMBIAYAAN LEMBAGA KEUANGAN PADA PENGEMBANGAN AGROINDUSTRI NILAM DI ACEH JAYA - Uswatuh Hasanah Nura; Nurita Puri (Jurnal Bionatural, 2025)
This study aims to identify the perception of patchouli farmers regarding financial institution financing in the development of patchouli agroindustry. The research method used consists of observational data and interviews by designing a set of questions in the form of a questionnaire distributed to 40 patchouli farmers. The data were obtained from both primary and secondary sources, and were then analyzed using descriptive qualitative and quantitative methods. The results show that the perception of patchouli farmers toward financial institution financing for the development of the patchouli agroindustry is generally negative or considered difficult and unsupportive. Only 8 farmers perceived the financing process as easy, while 32 farmers perceived it as difficult.